(untitled) (Journal of Economic Research & Business Administration, 2015)
There were considered basic provisions of criticism of the concept of resource curse. Attempt of the analysis of the reason of rejection of this criticism by considerable part of scientific community was made. Some tendencies of modern economic science explaining the reasons of upholding of the concept of resource curse in the conditions of a decline of a raw supercycle and other symptoms of structural crisis in world economy were revealed. The author’s position concerning the reasons of loss of relevance of the concept of resource curse in its traditional interpretation was proved. Author’s vision of possible reconsideration of the content of concept of resource curse was formulated.